Aortic Arch Reconstruction in Infants Using Autologus Pericardium - Y. Truba; A. Dovhaliuk; I. Dziuryi; O. Golovenko; V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2020)
Background. Aortic arch hypoplasia is a congenital anomaly of the development of the aortic arch characterized by hemodynamically significant narrowing of one or more segments of the aortic arch. This defect occurs either as an isolated condition or combined with other congenital heart defects. The materials used to enlarge aorta for successful repair and prevention of postoperative complications range from the patient’s own aortic tissue (in most cases) to other materials (autopericardium, xenopericardium, pulmonary artery tissues, synthetic patches). An autologous pericardial patch is the most common, available and cheap option.The purpose of this work is toanalyze immediate and long-term results of our experience using autologous pericardium to reconstruct the aortic arch.Materials and methods. From 2011 to 2019 at the National M.M. Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine and Ukrainian Children’s Cardiac Center 16 infants underwent aortic arch repair using autologous pericardial patch. The group included 6 (37.5%) male and 10 (62.5%) female patients. The mean age of the patients was 1.3 ± 0.9 months (from 0.06 to 4.5 months), the average body weight was 3.8 ± 1.6 kg (from 2.2 to 8.7 kg). The average body surface area was 0.24 ± 0.05 m?. Antegrade selective cerebral perfusion was performed in all the patients during the aortic arch reconstruction.Results. Hospital mortality was 6.2% (n = 1). The cause of death was not related to the reconstruction technique. The average duration of cardiopulmonary bypass was 142.5 ± 38.5 minutes, the aortic cross-clamp time was 76.9 ± 33.7 minutes, and the time of selective cerebral perfusion was 50.4 ± 25.4 minutes. Six patients (37.5%) in the early postoperative period had delayed sternal closure. According to echocardiographic data at discharge, the average pressure gradient at the site of aortic arch reconstruction was 15 ± 5.5 mm Hg, the left ventricular ejection fraction was 65.9 ± 5.9%.The mean follow-up period ranged from one month to 6.1 years (mean 2.8 ± 2.3 years). There were no deaths in the long-term period. Four (25%) patients developed aortic arch restenosis in the postoperative period. One patient presented with an aortic arch aneurysm 1 month after the initial operation. There were no cases of compression of the trachea, main bronchi, neurological complications in the follow-up period.Conclusions. The use of autologous pericardium in aortic arch reconstruction is an effective and safe procedure for infants with good immediate and long-term results. The study showed that autologous pericardium may be an acceptable alternative to reconstruct the aortic arch. A large percentage of reinterventions encourages more thorough removal of ductal tissues and determining the size of the autopericardial patch.